2011
DOI: 10.1002/ca.21188
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the accessory soleus muscle: A literature review, cadaveric study, and imaging study

Abstract: The accessory soleus muscle (ASM) has been an unusual anatomical variant since its first recordings in Guy's Hospital Reports of the early nineteenth century. Individuals with an ASM may present with symptoms of pain and/or swelling and were often misdiagnosed as soft-tissue tumors such as hemangioma, sarcoma, or lipoma. The aim of our study was threefold: (1) to review the cadaveric and clinical literature to determine the reported prevalence of ASM; (2) to conduct a cadaveric study investigating the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This condition is more frequently unilateral than bilateral (Sookur et al., ) and more common in men than women (Downey & Siegerman, ). Its prevalence varies from 0.7% to 15% (Hatzantonis et al., ; Del Nero et al., ). Historically, ASM used to be identified by surgical exploration, but presently it is diagnosed based on imaging techniques, such as magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…This condition is more frequently unilateral than bilateral (Sookur et al., ) and more common in men than women (Downey & Siegerman, ). Its prevalence varies from 0.7% to 15% (Hatzantonis et al., ; Del Nero et al., ). Historically, ASM used to be identified by surgical exploration, but presently it is diagnosed based on imaging techniques, such as magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…The soleus, gastrocnemius, and plantaris were separated from the bones (femur, tibia, and fibula) en bloc , and the soleus was then separated from the other muscles. The accessory soleus, which arises from the surface of the soleus and attaches to the calcaneus independently from the calcaneal tendon (Featherstone, 1995; Hatzantonis, Agur, Naraghi, Gautier, & McKee, 2011), was not found in the cadavers used in this study. The anterior and posterior surfaces of the muscles were cleaned by removing soft connective tissue.…”
Section: Methodsmentioning
confidence: 80%
“…Literature reviews revealed a higher prevalence of this finding among men (58% of cases) 10. Although debatable, it may be suggested that the greater number of symptomatic cases are reported in men due to greater muscle trophism and denser muscle fascia among males.…”
Section: Discussionmentioning
confidence: 92%